Two anonymous Byzantine romances about the Trojan War
1 online resource (106 pages)
Keywords: This volume provides the first English translations of The Tale of Troy and The Tale of Achilles, two medieval Greek romances by anonymous authors of the 14th/15th centuries that narrate the lives and loves of Achilles and Paris before and during the Trojan War.Set in the deep past of Greek mythology, these poems follow Achilles and Paris through their childhoods and their first stirrings of romance to the events that brought them to Troy, where both ultimately died. These tales, however, are also deeply of their own time, the late Byzantine period. A scholarly yet accessible introduction provides the political, historical, and literary contexts that shaped the production of these marvelous texts. Particular attention is given to intercultural exchanges in the late Byzantine period, marked by invasions of Crusaders and Ottomans who left a lasting impact not just on the political structures of the eastern Mediterranean but also on its literary production, introducing new words, new chivalric ideals, and new genres.These translations aim to make these poems accessible to anyone with an interest in the Trojan War; medieval romances; the literature of the Byzantine Empire; or the lives of Achilles, Paris, Helen, and other famous heroes of Greek myth.